Cultural similarity and dissimilarity in intercultural conflicts - Lauwo, George (2015)
This study investigated cultural similarity and dissimilarity in intercultural conflicts, by focusing on how a mediator understands cultural difference in the process of mediation. Intercultural conflict occurs when cultural worldviews of an individual or group are incompatible with the worldviews of another cultural group within the same community. Special interest has been on social inequality, stereotypes and ingroup outgroup tension as causes of intercultural conflicts. Participants for this study were qualified mediators from South Africa. In order to understand their practice environment and mediation landscape in general, community conflict in South Africa was studied. The findings revealed that cultural similarity and dissimilarity exist in every conflict, and it surfaces in the early sessions of the mediation process. A mediator is therefore compelled to familiarize with cultural differences by analyzing nature of the dispute, checking background of the parties in conflict and observing the disputants. Factors such as race/ethnicity, language, age and education of the individuals in a group in conflict are indicators used to identify cultural similarity and dissimilarity. Similarity in culture tends to draw party members together, enabling cooperation in narrowing the issues and uncovering underlying interests and needs, which makes facilitating for a resolution easy. Cultural understanding by a mediator helps to avoid mediation breakdown.